2008
DOI: 10.1090/s0002-9947-08-04473-5
|View full text |Cite
|
Sign up to set email alerts
|

A probabilistic approach to bounded/positive solutions for Schrödinger operators with certain classes of potentials

Abstract: Abstract. Consider the equationFor certain classes of potentials V , we use probabilistic tools to study the bounded solutions and the positive solutions for (*). A primary motivation is to offer probabilistic intuition for the results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…If we denote by L the generator of the Lévy process ξ = (ξ s ) s≥0 then at least formally the function h is harmonic for the operator L − f , which is a more general version of the Schrödinger operator above. This connection has been successfully exploited in the context of Brownian motion in Pinsky, R. (2008).…”
Section: Introductionmentioning
confidence: 99%
“…If we denote by L the generator of the Lévy process ξ = (ξ s ) s≥0 then at least formally the function h is harmonic for the operator L − f , which is a more general version of the Schrödinger operator above. This connection has been successfully exploited in the context of Brownian motion in Pinsky, R. (2008).…”
Section: Introductionmentioning
confidence: 99%
“…It is known [11], [2] that the following probabilistic condition is equivalent to the Liouville property: …”
Section: Introductionmentioning
confidence: 99%
“…For example, recently, it was shown in [6] that if the Liouville property for (1.1) does not hold, and if u solves (1.1) and satisfies 0 < c 1 ≤ u ≤ c 2 , then for any W ≥ 0 and any j ≥ 1, the j-th negative eigenvalue of the operator − [2], [4], [11]). In [11] it was pointed out that results in [3] show that (1.5) is necessary and sufficient for the Liouville property to hold for the class of functions V 0 decaying at least quadratically: 2 , for some c > 0. Furthermore, it was shown that this result is sharp.…”
Section: Introductionmentioning
confidence: 99%